Translation, content validity and internal structure of the Brazilian version of the Adolescent Resilience Questionnaire (B-ARQ) - Genara Brum Gomes; Luisa Gatti-Reis; Matheus França Perazzo; Marisa Alves Araújo; Flávio Freitas Mattos; Deirdre Gartland; Saul Martins Paiva; Isabela Almeida Pordeus (PLoS ONE, 2025)
Resilience refers to one’s ability to face life’s challenges and achieve positive outcomes, and has drawn increasing interest from researchers and policymakers. The Adolescent Resilience Questionnaire (ARQ) is a measure that assesses resilience in adolescents according to a multidimensional perspective, encompassing its several different domains. This cross-sectional study aimed to translate and evaluate the measurement properties of the Brazilian version of the ARQ (B-ARQ) for use with Brazilian adolescents. Two native speakers in Brazilian Portuguese language who were also fluent in English language translated the ARQ from English into Portuguese. A committee of experts in validation studies compared the translated versions. A summarized version was produced and back-translated by a translator native of the English language and fluent in Portuguese. The B-ARQ was pre-tested in a sample of 21 adolescents. An expert committee considered the suggestions and defined the final version of the instrument, which was tested in a sample of 210 adolescent students from public and private schools in the city of Dom Pedrito, Brazil. All students filled out the 88-item instrument as well as a socio-demographic questionnaire. Statistical analysis included descriptive statistics of all variables (frequency distribution, floor, ceiling effects), internal consistency, and confirmatory factor analysis of the version with 88 items and the shortened version with 49 items. The short version with 49 items was validated in a cross-sectional study in an adolescent population of high school students using exploratory factor analysis in the Unites States. The 88-item ARQ had poor structural validity with unsatisfactory model fit indices. Therefore, the investigation focused on the short 49-item version of the ARQ (B-ARQ-SV). The final model presented satisfactory RMSEA = 0.042 (p = 0.994, 90% CI: 0.037–0.047) and SRMR of 0.076, despite the low CFI (0.878). The internal consistency was estimated with McDonald’s Omega for each factor: Confidence (ω = 0.480), Negative Cognition (ω = 0.588), Empathy/tolerance (ω = 0.295), Emotional insight (ω = 0.425), Social Skill (ω = 0.235), Family Domain Connectedness (ω = 0.785), Family Domain Availability (ω = 0.847), Peers Domain Connectedness (ω = 0.719), Peers Domain Availability (ω = 0.402), School Domain Supportive environment (ω = 0.677), School Domain Connectedness (ω = 0.013), Community Domain Connectedness (ω = 0.791). One scale showed a ceiling effect (frequency higher than 15.0%), but we identified no critical floor effect. The B-ARQ-SV is a valid (in terms of content and structural validity) and reliable (in terms of internal consistency) measurement instrument to assess resilience in Brazilian adolescents.